Tanggung Gugat Atas Jual Beli Pulau Lantigiang Berdasarkan Syarat Sah Nya Perjanjian - Arum Prabaning Tyas (Jurnal Selat, 2021)
Lantigiang Island, uninhabited island covering an area of ​​5.6 hectares located in Jinato Village, Takabonerate District, Selayar Islands Regency, South Sulawesi. This island is reported to have been sold by Syamsul Alam, who claims to be the owner of the island, to Asdianti, a resident of the Selayar island for Rp. 900,000,000 (Nine Hundred Million Rupiah). Lantigiang Island is included in the Takabonerate National Park area and is a protected conservation area. The conservation area aims to conserve the forest and the life in it, including the diversity of plants and animals and their ecosystems so that their functions can be carried out optimally. According to the agrarian regime, conservation areas are not for sale in general. This writing is compiled through a normative juridical analysis method with a statue approach, a conceptual approach and a case approach. Based on these three methods, it is necessary to observe and analyze which party is most responsible for the buying and selling process of the island of Lantigiang.